Population-Based Surveillance for Hypermucoviscosity Klebsiella pneumoniae Causing Community-Acquired Bacteremia in Calgary, Alberta - Gisele Peirano; Johann DD Pitout; Kevin B Laupland; Bonnie Meatherall; Daniel B Gregson (Canadian Journal of Infectious Diseases and Medical Microbiology)
The characteristics of hypermucoviscosity isolates among Klebsiella pneumoniae causing community-acquired bacteremia were investigated. The hypermucoviscous phenotype was present in 8.2% of K pneumoniae isolates, and was associated with rmpA and the K2 serotype; liver abscesses were the most common clinical presentation. The present analysis represents the first population-based surveillance study of hypermucoviscosity among K pneumoniae causing bacteremia.